RESPON TERHADAP HUKUM PERKAWINAN DI INDONESIA - Hermawati, Nety (Al-Mizan, 2015)
Historical development of the law of marriage in Indonesia experienced a long process until it forms into a law. Various responses of the law appears to be related to the formation of this marriage. This article discusses the public response to the marriage law in Indonesia. This study uses the approach of legal history. The results showed that the birth of the marriage law in Indonesia canât be separated from political interference and the existence of womens and feminist Indonesia. Then in this era of reform, gender activists would like to reconstruct Law 1 of 1974.